LEXICAL AND STYLISTIC FEATURES OF TOURISM TERMS IN ENGLISH AND UZBEK - Dildora Xolboyeva (Web of Journals Publishing, 2025)
This article examines the stylistic aspects of tourism terms in English and Uzbek. There are another views of the concept of the tourist sphere of the scientists. Traditionally, in linguistics, a genre is considered to be a set of features such as the style of presentation of the text, the form of speech, and generally accepted traditional methods of constructing speech and combining speech units.
Keywords: Guidebook, brochure, features, genres.